The implementation of PBL-integrated blended learning to improve senior high school students critical thinking skills on the human reproductive system instruction - Y Hildawati; D Priyandoko; Kusnadi Kusnadi (Pascasarjana Universitas Pendidikan Indonesia, 2021)
The ability to think critically is one of the competencies students must possess to be able to compete in the era of globalization. This study aimed to determine the increase in students' critical thinking skills with the implementation of PBL- integrated blended learning to the topic of the human reproductive system. The method used was a weak experiment with the research design of The one group pretest-posttest design carried out in class XI students in one of the state high schools in Bandung. Critical thinking skills data were captured through an essay test with the questions’ indicators are based on the Inch framework. Increased students' critical thinking skills were obtained based on the results of the pretest and posttest analyzed by computing the N-gain. Based on N-gain calculations, students' critical thinking skills showed an increase of 0.73 (high category). This shows that PBL-integrated blended learning could improve students' critical thinking skills on the topic of the human reproduction system